TANTANGAN DAN PENDUKUNG INTEGRASI TEKNOLOGI DIGITAL DALAM IMPLEMENTASI KURIKULUM MERDEKA: SEBUAH TINJAUAN LITERATUR SISTEMATIS - Inggrid Puji Astri; Emilda Sulasmi; Faisal Rahman Dongoran (Pedagogi: Jurnal Ilmiah Pendidikan, 2026)
The implementation of Indonesia's Merdeka Curriculum relies on digital technology integration to create flexible and student-centered learning. This systematic review synthesizes evidence from 21 research articles (2019-2025) to map key enabling factors and challenges. Results reveal three key enablers: the effectiveness of specific digital tools (such as interactive e-worksheets and LMS), the alignment of technology with the curriculum's pedagogical principles (differentiated and project-based learning), and curriculum flexibility that provides space for innovation. Conversely, five systemic challenges were identified: digital infrastructure disparities, limited teacher techno-pedagogical competence (TPACK), scarcity of contextual digital learning resources, complexity of authentic technology-based assessment, and policy fragmentation across government levels. In conclusion, digital transformation requires an integrated approach that simultaneously addresses infrastructure gaps, empowers teachers through continuous TPACK development, strengthens digital content ecosystems, and improves policy coordination. Future research directions include longitudinal studies to measure long-term impact, design-based research for curriculum-specific digital tools, and analysis of implementation policies at the regional level.